2013
DOI: 10.1158/0008-5472.can-12-2633
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like Kinase 1: A Potential Therapeutic Option in Combination with Conventional Chemotherapy for the Management of Patients with Triple-Negative Breast Cancer

Abstract: Breast cancers are composed of molecularly distinct subtypes with different clinical outcomes and responses to therapy. To discover potential therapeutic targets for the poor prognosis-associated triple-negative breast cancer (TNBC), gene expression profiling was carried out on a cohort of 130 breast cancer samples. Polo-like kinase 1 (PLK1) was found to be significantly overexpressed in TNBC compared with the other breast cancer subtypes. High PLK1 expression was confirmed by reverse phase protein and tissue … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
194
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 166 publications
(208 citation statements)
references
References 46 publications
5
194
0
Order By: Relevance
“…This further suggests that association of high EZH2 with cancer aggressiveness might reflect the increased cell proliferation occurring in advanced stages of prostate cancer (e.g., see Tomlins et al 2007). A similar analysis on a breast cancer cohort comprising 146 samples from the four main molecular subtypes (Maire et al 2013) confirmed that EZH2 expression correlates with proliferation markers (Supplemental Fig. S2B).…”
Section: H3k27me3 Homeostasis Is Compromised In Breast Cancermentioning
confidence: 62%
“…This further suggests that association of high EZH2 with cancer aggressiveness might reflect the increased cell proliferation occurring in advanced stages of prostate cancer (e.g., see Tomlins et al 2007). A similar analysis on a breast cancer cohort comprising 146 samples from the four main molecular subtypes (Maire et al 2013) confirmed that EZH2 expression correlates with proliferation markers (Supplemental Fig. S2B).…”
Section: H3k27me3 Homeostasis Is Compromised In Breast Cancermentioning
confidence: 62%
“…In addition, the prognostic relevance of genes like PIK3R1, NEK3, SASH1, and RASA3 on chromosome 17p13 was also defined for the intestinal subtype (9). The intestinal subtype specific aberration patterns including deletion of 5q, gain of 3q21-26 and overexpression of CCNL1 and KLF5 and downregulation of PLK2 and PPP3CA were also identified in other tumor types (29,(33)(34)(35). Furthermore, subtyping of periampullary adenocarcinomas using the PAM50 classifier identified a subgroup of pancreatobiliary tumors that are basal-like with worse prognosis as identified by Moffitt and colleagues as well; however, the Collisson's subtypes were not prognostically different in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports with BI 2536 have shown that inhibition of PLK1 in vitro also boosts the antineoplastic effects of other chemotherapeutics, such as temozolomide (TMZ) [30], MTX and CDDP [31], DXR and cyclophosphamide [32], docetaxel [33], and histone deacetylase inhibitors [34], among others. It is well recognized that treatment efficacy (irrespective of the tumor type) is often achieved by combining agents with diverse mechanisms of action and different spectra of toxicity.…”
Section: Discussionmentioning
confidence: 99%